Bauran Promosi Digital Restoran All You Can Eat Lokal dalam Menarik Minat Beli Pelanggan - Christine Farnanda; Firdanianty Pramono; Karina Pramita Ningrum (Universitas Pakuan, 2026)
This study aims to analyze the promotional mix of Gyuniku Indonesia Restaurant (RGI), its obstacles, and the elements that play a role in attracting customer interest. The research employed a descriptive qualitative adopted Kotler and Armstrong’spromotional mix, which includes advertising, sales promotion, direct marketing, personal selling, and public relations. Data were collected through semi-structured interviews with the RGI’s owner as the primary informant and customers as supporting informants, and were further reinforced by source triangulation. Field observations and documentation of promotional media were also used as supplementary data. The findings reveal that sales promotion is the most influential element in increasing customer purchase interest. Programs such as Buy 4 Get 1, Lunch Promo IDR 85,000, and a 10% discount effectively attracted consumer attention. In addition, public relations efforts through direct customer engagement and external partnerships helped strengthen the restaurant’s positive image. The main challenges faced by RGI are limited resources and narrow media reach. In conclusion, RGI’s promotional mix is relevant but needs improvement in media reach and promotional intensity to remain competitive in the AYCE market. These findings are expected to provide practical insights for culinary business practitioners in designing more effective marketing communication strategies.